The Impact of Environmental Performance on Economic Growth: A Study of ASEAN Countries - Lestari, Rini; Ramdani, Boyke Rahmat; Purnamasari, Pupung; Nurfahmiyati, N. (International Journal of Energy Economics and Policy, 2023)
The aim of this study is to explore the effect of environmental performance on economic growth, the effect of environmental performance on health expenditure, the effect of health expenditure on economic growth, and the role of health expenditure in mediating the effect of environmental performance on economic growth. The study uses a quantitative research method with a verification approach and utilizes secondary data from the World Bank Indicator. Purposive sampling has been used in this study, and the sample involved countries from the ASEAN region. The statistical analysis tool used in this study is EViews version 12. The results indicate that environmental performance has an impact on economic growth, that environmental performance affects health expenditure, that health expenditure has an impact on economic growth, and that health expenditure can mediate the impact of environmental performance on economic growth. According to the study's findings, ASEAN companies must reduce the environmental damage caused by their activities in order to improve their environmental performance, which will help boost economic growth in ASEAN countries